Physiological and clinical effects of electroacupuncture anaesthesia of abdomino-pelvic regions in goats - BIHARI, AWADH; KUMAR, AMRESH (The Indian Journal of Animal Sciences, 2013)
The electroacupuncture stimulation of combination of acupoints LI-4, Liv-14, GB-34, BL-30, GV -20 and Tianping (group 1); LI-11, Liv-4. GB-34, BL-3D, GV-20 and Tianping (group 2); and ST-36, SP-6. GB-34, BL-30. GV-20 and Tianping (group 3) at a current of 3-5 volts in adjustable wave form and frequencyof 130-150 Hz brought about complete and good anaesthesia and muscle relaxation at flank, ventrolateral abdominal region, pelvic and perineal regions, medial aspect of thigh, teats and udder in animals of group 3. A moderate degree of anaesthesia of flank, ventrolateral abdomen, medial aspect of thigh along with pelvic and perineal regions with poor anaesthesia of teat and udder was observed in other groups. The onset of anaesthesia occurred in 18.10-+0.30 to 19.50Â±0.45 min. Anaesthesia was maintained as long asstimulation lasted. A significant increase (P0.05) increase in respiration, rectal temperature, mean arterial blood pressure with minor alteration in central venous pressure, ECG and acid-base status was seen after electroacupuncture stimulation of these acupoints in various groups of animals. No significant changes were seen between these groups of animals. The recovery was quick and occurred in 12.45Â±0.54 min after discontinuation of electrostimulation.